Potential impacts of acupuncture on motor function recovery after ischemic stroke: insights from basic and clinical studies - He, Jia-Ling; Ma, Liang-Xiao; Wen, Jing-Si; Zhuang, Yu-Xin; Qian, Xu; Ma, Ling-Hui; Xiu, Jing-Yun; Wang, Xiu-Yan; Chen, Meng-Yu (Frontiers in Cellular Neuroscience, 2025)
Ischemic stroke is one of the leading causes of death and long-term disability worldwide. A significant proportion of stroke survivors experience persistent motor impairments, which severely affect their quality of life and cause heavy social and economic burdens. Acupuncture has increasingly gained attention due to its remarkable efficacy in promoting motor function recovery after stroke, and it has been progressively endorsed as a post-stroke treatment option by clinical guidelines of numerous countries, despite its underlying mechanism is not yet fully understood. This review systematically evaluates existing basic and clinical studies to explore the potential mechanisms of acupuncture’s effects on motor function recovery after ischemic stroke and the optimal clinical strategies. Emerging evidence demonstrates that acupuncture-mediated post-stroke motor recovery is primarily attributed to its roles in restoring energy metabolism, inhibiting neuroinflammation, preventing neuronal apoptosis, promoting neuronal repair and regeneration, and regulating neuronal excitability. Additionally, individualized acupuncture modality involving syndrome-based selection of acupoints and stimulating methods is crucial for better rehabilitation outcome. Our findings elucidate the multidimensional impacts of acupuncture on motor function restoration following ischemic stroke, furnishing robust evidence and theoretical foundation for its clinical application.